2020
DOI: 10.1186/s40662-020-00185-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel ophthalmic viscosurgical device-free phakic intraocular lens implantation makes myopic surgery safer

Abstract: Purpose: To assess the efficacy and safety of a novel ophthalmic viscosurgical device-free (OVD-free) method for posterior chamber phakic intraocular lens (PIOL) implantation in myopic eyes. Methods: In this retrospective cohort study, the medical records of myopic eyes that underwent PIOL (Implantable Collamer Lens, ICL) implantation for myopia correction at the Eye Hospital of Wenzhou Medical University between May 2015 and March 2017 were reviewed. A total of 49 eyes with complete data that met follow up re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
0
15
0
3
Order By: Relevance
“…More than 120,000 ICL implantation surgeries are performed in over 60 countries annually, making the vault, an indicator of postoperative safety, particularly important [ 23 ]. In the current study, we aimed to assess the early changes in the ICL vault in the first month, starting at 2 h after ICL implantation.…”
Section: Discussionmentioning
confidence: 99%
“…More than 120,000 ICL implantation surgeries are performed in over 60 countries annually, making the vault, an indicator of postoperative safety, particularly important [ 23 ]. In the current study, we aimed to assess the early changes in the ICL vault in the first month, starting at 2 h after ICL implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Lisa [36] reported a rate of 1.7% at 12 months after surgery. Pan [25] found that the rate was approximately 4.6% at 3 months after surgery. In this study, the loss rate of corneal endothelial cells in the pure group was approximately 2%, whereas that in the standard group was approximately 2.3%, at 3 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Bluementhal [21] , Tak [22] , Fatih [23] , Bardoloi [24] and other researchers have used various ACM devices to avoid the use of OVDs during phacoemulsi cation cataract extraction or intraocular lens implantation. Pan [25] introduced ICL implantation with continuous infusion and a single-handed ACM. Its safety and effectiveness have been con rmed.…”
Section: Discussionmentioning
confidence: 99%
“…Bluementhal [ 22 ], Tak [ 23 ], Fatih [ 24 ], Bardoloi [ 25 ], and other researchers have used various ACM devices to avoid the use of OVDs during phacoemulsification cataract extraction or intraocular lens implantation. Pan [ 26 ] introduced ICL implantation with continuous infusion and a single-handed ACM. Its safety and effectiveness have been confirmed.…”
Section: Discussionmentioning
confidence: 99%